ScientISST CORE: A novel hardware development platform for biomedical engineering - Leonor Pereira; Francisco de Melo; Frederico Almeida Santos; Afonso Fortes Ferreira; Hugo Plácido da Silva (HardwareX)
Today, the use of biosignals is no longer limited to the traditional healthcare and medical domains, thanks to the application of biomedical engineering principles and devices in other domains, paving the way to the broader field of physiological computing. The increasing interest from the global engineering community, together with the challenges associated with the stringent requirements of biosignal acquisition, have motivated the development of enabling low-cost instruments for physiological sensing. Still, the use of some of these instruments in experimental activities and practical projects is still bounded by the cost and limited access to adequate support materials. In this paper, we present a novel low-cost hardware architecture especially designed for biosignal acquisition, and pre-programmed with a firmware optimized for real-time data acquisition and streaming. Our approach can be used seamlessly with available open-source software and APIs, without requiring extensive knowledge of electronics or programming. We also describe a series of tests conducted to evaluate the performance of this device, as a way of verifying its suitability for use in engineering and scientific work. Overall, the results presented here show that there is no loss of data in communication, accurate sampling rates, and high noise rejection capabilities in the tested conditions.